2013
DOI: 10.1364/ao.52.006616
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength generation based on a mode-locked fiber laser using carbon nanotube and fiber Fabry–Perot filter

Abstract: In this paper, a novel and compact configuration of stable multiwavelength generation with a uniform wavelength interval is proposed for the first time to our knowledge. It employs a mode-locked fiber laser using a carbon nanotube and spectrum-slicing technique. A flat rectangular optical output spectrum is demonstrated by adjusting the dispersion value of the fiber-loop cavity and the pump power. With a fiber Fabry-Perot filter, 33 wavelengths with 0.2 nm spacing are obtained among the power uniformity of 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…On the other hand, multi-wavelength pulsed fiber lasers have received considerable attention for their versatile applications, including wavelength division multiplexer (WDM) fiber communication systems, photonic component characterization and optical signal processing [13][14][15][16]. Recently, Zhang et al reported a triple-wavelength passively mode-locked fiber laser in an all-normal dispersion cavity with a semiconductor saturable absorber mirror (SESAM) [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multi-wavelength pulsed fiber lasers have received considerable attention for their versatile applications, including wavelength division multiplexer (WDM) fiber communication systems, photonic component characterization and optical signal processing [13][14][15][16]. Recently, Zhang et al reported a triple-wavelength passively mode-locked fiber laser in an all-normal dispersion cavity with a semiconductor saturable absorber mirror (SESAM) [17].…”
Section: Introductionmentioning
confidence: 99%